Bioprospecting Bacteriocinogenic Lactic Acid Bacteria from Algerian Raw Goat Milk and Traditional Cheeses - Boutaleb , Naima; Mechai, Abdelbasset; Arhab, Rabah; Debabza, Manel (HAYATI Journal of Biosciences, 2026)
Artisanal fermented dairy preparation represents one of the oldest and most prevalent methods of food preservation, having enabled rational management of valuable food resources for millennia across various cultures worldwide, particularly those of the southern Mediterranean countries. Bacteriocinogenic lactic acid bacteria (LAB) that are contained in traditional fermented milk are considered good sources of promising antimicrobial bioactive compounds. A total of 58 LAB were isolated and identified based on phenotypic characteristics and then tested for their antibacterial effectiveness against both Gram-positive and Gram-negative bacteria that cause food spoilage. Eight strains among selected LAB produce bacteriocin-like inhibitory substances (BLIS), which have a broad antibacterial spectrum against tested species. The strains were identified by 16S rRNA gene sequence analysis. All generated BLISs were fully inactivated by proteolytic enzymes while remaining unaffected by catalase, indicating their proteinaceous nature. The BLIS produced by Lactiplantibacillus plantarum NBC101174 was concentrated by the addition of ammonium sulfate to a final concentration of 80%, which allowed for an increase in the specific activity of the bacteriocin from 21.05 to 106.00 AU/mg, increasing the specific factor of 5.04 fold. The inhibitory substance produced by Lpb. plantarum NBC101174 exhibits a bactericidal effect, leading to cell lysis and a 99.9% lethality rate against the indicator strain. The findings of the current study could increase our understanding of bacteriocinogenic LAB diversity. It could also be concluded that LAB isolated from Algerian fermented milk provides a promising source for bacteriocins that can be used safely as bio-preservation of various foods produced under different storage conditions.